ENHANCING COMPETITIVENESS STRATEGIES FOR SMES THROUGH DIGITAL MARKETING IN KALIWATES SUB-DISTRICT, JEMBER REGENCY (CASE STUDY: NAWASENA CLOTHING) - Ahmad Lutfi; Moch. Chotib, Misbahul Munir (Adisam Publisher, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in driving economic growth, particularly in developing regions like Kaliwates, Jember. This research investigates strategies to enhance the competitiveness of SMEs through digital marketing, focusing on Nawasena Clothing as a case study. The study employs a qualitative approach, utilizing interviews and surveys to gather data from SME owners and digital marketing experts. Findings of this research is Nawasena Clothing, a case study in Kaliwates District, Jember Regency, highlights the critical importance of competitive strategies for SMEs in navigating the dynamic era of digital marketing. Demonstrating effective implementation of integrated digital marketing strategies, Nawasena Clothing expanded market reach and increased sales significantly. Their success underscores the pivotal role of platforms like Instagram, Facebook, and online marketplaces such as Shopee and Tokopedia in enhancing brand exposure and engaging potential consumers effectively. Beyond product promotion, Nawasena Clothing emphasized brand image building through compelling visual content and personalized shopping experiences. Supported by deep consumer behavior analysis and local market trends, their strategy enables informed decision-making in product development, promotional adjustments, and customer interactions, ensuring continued relevance in Kaliwates' competitive fashion industry